Global social contract: On the road to an economically-sound. Ethics of globalization - Ingo Pies (Wittenberg-Zentrum für Globale Ethik, 2003)
Forced individualization, increasing pluralism and overwhelming practical constraints, particularly in the business arena, characterize our modern world. Ruthlessness, especially in competition, often seems to be the order of the day. Against this background, many people ask themselves whether business practice and moral principle contradict one another. I am going to answer this question not from a moral but from an economic point of view. It would be, in the most literal sense, a “waste of capital” not to make use of the wisdom of the great world religions and the ancient tradition of ethical reflection in theology and philosophy. In my opinion, it is one of foremost responsibilities of modern ethics to tap this stock of traditions, for the sake not of the past but of the future. Let me now go directly “in medias res”. I would like to present some of the ideas which will guide me in my work both at the University and at the Wittenberg Center. To this end, I have chosen the programmatic title “Global Social Contract”, which for the time being I intend literally: The phrase stands for the social contract of a global society.
urn:nbn:de:gbv:3:2-4472
Keywords: 330